Premarital screening and genetic counseling program: Studies from an endogamous population - Bener, Abdulbari; Al-Mulla, Mariam; Clarke, Angus (Wolters Kluwer, 2019)
Background: Studies in Arab countries have shown a significant lack of knowledge of Premarital Screening and Genetic Counseling (PMSGC) Program. PMSGC can identify and modify, through prevention and management, some behavioral, medical, and other health risk factors known to impact pregnancy outcomes. Objective: The aim of this study was to explore the knowledge, attitudes, and practice of Qatari’s toward the premarital screening program and shedding more light on a complex matter. Materials and Methods: A cross?sectional study based on Hospitals and Primary Health Care Centers. A total sample of 1246 participants was surveyed, and 873 participants (70.0%) expressed their consent to participate in the study during January 2013–May 2014. The questionnaire based on sociodemographic data and for responses, on the PMSGC program knowledge, attitude, and practice statements. In addition, questions were asked regarding the services, activities, and how to attract and motivate the PMSGC program. Results: The mean age and standard deviation (SD) of the males’ age were 30.4 ± 6.50 and the mean and SD of females’ age were 31.08 ± 5.98. There were statistically significant differences between males and females with regard to age, educational status, occupation status, household income, consanguinity, body mass index, cigarette smoking, and Shisha smoking. There were no any statistically significant differences between males and females regarding sickle cell anemia and thalassemia, glucose?6?phosphate dehydrogenase deficiency cystic fibrosis, homocystinuria, HIV, and hepatitis. The response to the ''Why proceeding through high-risk marriage?'' by gender, males and females responded statistically significant differences (P = 0.019). The step?wise multivariate regression analyses as predictors for knowledge of PMSGC program revealed that age, educational level, the lack knowledge of genetics counseling, parental interventions for cousin marriage decision, positive test results affect and change marriage decision, religious impact, household income, consanguinity, hereditary diseases knowledge, occupational status, and love factors were considered as the main factors associated with the premarriage screening and genetics counseling after adjusting for age, gender, and other variables. Conclusion: The current study revealed that knowledge and attitude regarding PMSGC program were low in population. Motivation, enforcement, and implementation of program at the school and university educational campaigns are vital. Improved counseling and adding new topics for counseling on genetic, chronic, and mental illness; building healthy families; and reproduction and fertility are considered to be top priorities in community.
Keywords: Consanguinity; Qatar; Knowledge and Attitude; Premarital Screening Program; Premarital Testing